Pengaruh Faktor Ekonomi Makro dan Kinerja Keuangan Terhadap Nilai Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia pada Tahun 2018-2022 - Wijaya, Aldy Pranstanri; Askandar, Nur Shodiq; Mahsuni, Abdul Wahid (e_Jurnal Ilmiah Riset Akuntansi, 2024)
This research aims to analyze the influence of changes in macroeconomic factors and financial performance on the value of manufacturing companies in Indonesia. The population in this research are manufacturing companies listed on the Indonesia Stock Exchange in the period 2018 to 2022. The number of samples used in this research was 193 samples using a purposive sampling method. The company value variable is proxied by the Price Earning Ratio (PER), macroeconomic factor variables are proxied by inflation and exchange rates, financial performance is proxied by Return on Equity (ROE). The analytical tool used is multiple regression analysis, using SPSS 22.0 software. The results of this research show that ': (1) macroeconomic factors have a negative and insignificant effect on company value, (2) company performance has a negative and significant effect on company value. It is recommended for investors to consider when making investment decisions, so that macroeconomic variables and financial performance can be used as investment considerations.Keywords: Macroeconomic factors, financial performance, company value, investment.